Some Differences in the Saline Consummatory Behaviour of Acute and Chronic Sodium Deficient Rats - Smith, Donald F. (My University, 1968)
The effect of acute and chronic sodium deficiency on the saline appetitive behavior of rats was investigated using a brief exposure multistimulus taste test that was shown to eliminate post-ingestional factors. The chronically deficient adrenalectomized rats showed a distinct preference for dilute salt solution. The acutely deficient formalin injected animals generated saline acceptability curves which were similar to the normals, but increased their salt consumption overall by taking more trials. It is concluded that the sodium appetite of adrenalectomized rats is mediated, at least in part, by peripheral events.
Title: Some Differences in the Saline Consummatory Behaviour of Acute and Chronic Sodium Deficient Rats, Author: Donald F. Smith, Location: Thode